Practical demonstration of a RRAM memory fuse. (5th May 2021) - Serb, Alexander; Khiat, Ali; Prodromakis, Themis
Summary: Since its inception, the resistive random access memory (RRAM) fuse has been a good example of how small numbers of RRAM devices can be combined to obtain useful behaviors unachievable by individual devices. In this work, we link the RRAM fuse concept with that of the complementary resistive switch (CRS), exploit that link to experimentally demonstrate a practical RRAM fuse using TiO x ‐based RRAM cells, and explain its basic operational principles. The fuse is stimulated by trains of identical pulses where successive pulse trains feature opposite polarities. In response, we observe a gradual (analogue) drop in resistive state followed by a gradual recovery phase regardless of input stimulus polarity, echoing traditional, binary CRS behavior. This analogue switching property opens the possibility of operating the RRAM fuse as a single‐component step change detector. Moreover, we discover that the characteristics of the individual RRAM devices used to demonstrate the RRAM fuse concept in this work allow our fuse to be operated in a regime where one of the two constituent devices can be switched largely independently from the other. This property, not present in the traditional CRS, indicates that the inherently analogue RRAM fuse architecture may support additional operational flexibility through, for example, allowing finer control over its resistive state. Abstract : In this work, we present the analogue generalixation of the "complementary resistive switch." A conceptual description of the phenomenon is given, showing how the switching characteristics of the memristive devices affect the obtained behavior. We also experimentally demonstrate both regular bipolar switching and "fuse" switching whereby the system acts as a polarity change detector regardless of the direction of change (positive to negative of vice versa).